165 Novel ANO5 gene mutations, c.989dupT and c.2018A→G causing Limb Girdle Muscular dystrophy 2L. Issue 3 (9th February 2012) - Panicker, J; Lochmuller, H; Bushby, K; Straub, V; Hicks, D; Sarkozy, A; Ray, P
Abstract : A 41-year-old male presented with difficulty in walking on tiptoes and in standing for long periods and also noticed wasting of both his calves, forearm muscles and thighs for 2 years. There was no major past medical history, but there was family history of similar leg wasting and weakness in his father 20 years previously and was diagnosed to have possible Multiple sclerosis and Polio. Examination revealed symmetrically wasted calf muscles, quadriceps and forearms with weak dorsiflexion and plantar flexion of both feet and knee extension with preserved reflexes and sensations. MRI Scan of the Lumbar spine was normal. Serum creatine kinase levels were persistently more than 4000 units. Myopathic changes were noted on EMG in tibialis anterior and gastrocnemius on right side. Muscle biopsy of right quadriceps showed a Necrotising myopathy and no other abnormalties were noted on immunohistochemistry and immunoblotting. Genetic testing for mutations of dysferlin, Caveolin 3, Calpain 3, Facioscapulohumeral dystrophy and common mutations for Myofibrillar myopathy were negative. Genetic analysis of ANO5 gene showed two novel mutations, c.989dupT in exon 10 predicted to disturb the protein reading frame leading to premature termination codon and hence highly likely to be pathogenic and c.2018A→G in exon18 resulting in a substitution of neutral polar tyrosine with neutral polar cysteine. These mutations are previously unreported and are the likely explanation for the clinical presentation leading to a diagnosis of LGMD2L